Análise da Interdisciplinaridade de conteúdos produzidos em livros e artigos voltados ao ensino de bioquímica no ensino médio sob as orientações da BNCC, PCNs e RC - (:unkn) unknown (Brasil, 2024)
The study of biochemistry is extremely important within science, as it encompasses the disciplines of chemistry and biology in an interdisciplinary way. To guide the content taught, the Ministry of Education (MEC) has guiding documents, such as the National Common Curricular Base (BNCC), which is responsible for managing the content that is included in secondary education. The National Curricular Parameters (PCNs), which is an auxiliary document in the preparation of educational curricula and the Curricular Reference (RC), a reference document, responsible for highlighting the specific content for each state. From this context, the present work analyzed and highlighted the biochemistry contents on biomolecules, which can be taught in an interdisciplinary way between chemistry and biology in high school, emphasizing the main biomolecules: Proteins, Carbohydrates, Lipids and Nucleic acids. To this end, a qualitative analysis of the documents prepared by the MEC (BNCC, PCN and RC) was used to identify which contents were covered and which were the guidelines for their application. Based on this context, an analysis of textbooks and published articles that addressed the teaching of biochemistry was developed, identifying the content taught, the proposed methodology, interdisciplinarity and the relationship with the BNCC, the PCNs and the RC. Therefore, the work sought to demonstrate whether biochemistry content can be taught in an interdisciplinary manner, based on the guidelines contained in the BNCC, PCNs and RC. Regarding the results obtained, it can be seen that they were partially satisfactory, which was evidenced by the interdisciplinarity of the biochemistry discipline, in the books and articles analyzed. However, some problems compromised the results, such as the lack of approach in the classroom regarding these contents.
Bioquímica
Keywords: Livros didáticos; Textbooks; Biomoléculas; Biomolecules; Ciência; Science; Publicações; Publications.; Ciências da natureza